Indigenous communities of the province of Chimborazo, Ecuador: permanence of the shadow of the hacienda regime - Tuaza Castro, Luis Alberto (2014)
This paper analyzes current indigenous politics, from an approachto the indigenous communities historical process in the area of Guamote Totorillas, Ecuador. It is argued that after the dissolution of the hacienda system new forms of indigenous leadership emerged. The pervasiveness of ancient forms of leadership stemming from the hacienda system, though, prevent communities efforts to achieve unity and the design of a long term political project.